An Author’s Delusion in Victorian Canada: Richard Maurice Bucke and Transnational Publishing of Popular Science - Connor, Jennifer (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2021)
We know little about the transnational publishing experience of authors of books about scientific topics in Canada. This study therefore explores the nineteenth-century publication of a Canadian author’s manuscript in the United States and Great Britain: Man’s Moral Nature (1879) by Ontario physician Richard Maurice Bucke. Although this book is relatively unknown, Bucke’s personal records about this, his first book, provide insights into publishing processes, from finding a publisher through to understanding book production and copyright. As the book’s reception shows, Bucke not only was unable to position his scientifically-oriented book for his intended general readership but he also received criticism from medical colleagues for his attempt. Bucke’s emphasis on obtaining a North American readership, however, adds further evidence of a continental market described by book history scholars.